2019
DOI: 10.2174/2468187309666190906130115
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanocomposites of Nigella sativa Seeds Extract for Hepatocellular Carcinoma

Abstract: Background: Silver nanoparticles play a significant role in bioavailability and refining the compatibility of natural drugs in the treatment of various chronic diseases including different types of cancer. Objective: Green synthesis of silver nanocomposites of Nigella sativa seeds extract to evaluate the anticancer effects against hepatocellular carcinoma using HepG2 cell lines. Methods: The AgNCs were developed by treating aqueous extract of N. sativa seeds treated with silver nitrate (1mM) solution and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Biosynthesized silver nanoparticles and Piper nigrum extract showed promising anticancer activity against breast cancer cells (MCF-7) and human pharynx cancer cell line (Hep-2) [28]. Other findings revealed that silver nanoparticles from Nigella sativa seeds were found to be effective against hepatocellular carcinoma using HepG2 cell lines [40].…”
Section: Anticancer Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Biosynthesized silver nanoparticles and Piper nigrum extract showed promising anticancer activity against breast cancer cells (MCF-7) and human pharynx cancer cell line (Hep-2) [28]. Other findings revealed that silver nanoparticles from Nigella sativa seeds were found to be effective against hepatocellular carcinoma using HepG2 cell lines [40].…”
Section: Anticancer Activitymentioning
confidence: 98%
“…UV-visible spectrophotometry is a readily available technique allows fast identification and characterization of silver nanoparticles. It gives strong absorbance band known as surface plasmon resonance (SPR) in the range 400-500 nm due to the interaction between light and mobile surface electrons of silver nanoparticles [16,39,40].…”
Section: Uv-visible Spectrophotometrymentioning
confidence: 99%
“…Under the influence of the electric field, the velocity of the particles is evaluated at which they travel towards the electrodes [20]. AgNPs synthesized using seed extract of Nigella sativa and leaf extracts of Gloriosa superba and Cynara scolymus showed that particles possess negative charge with the potential of − 18.8 ± 0.372, − 27.0, and − 32.3 ± 0.8 mV respectively [50][51][52]. Zeta potential of the Phyla dulcis extract loaded silver nanoparticles was analyzed and values were between − 20 and − 24 mV indicated that the AgNPs are relatively stable [53].…”
Section: Zeta Potential Analysismentioning
confidence: 99%
“…Almatroudi et al (2020) also supported the former study and suggested that Ns-AgNPs showed significant cytotoxic ability and substantially killed human breast cancer cell (HCC-712) viability. In an in vitro test carried out using Ns-AgNPs on hepatocellular carcinoma, it has been observed that these nanoparticles possess a cytotoxic effect of p<0.05 with a 7.16 µg/ml IC 50 value (Usmani et al, 2019). It has been observed that Ns-AgNP at an amount of 12.5 µg/ml showed antibiofilm activity by 88.42% for Enterococcus faecalis, 84.92% for E. coli, 81.86% for Klebsiella pneumonia, 82.84% for Staphylococcus aureus, and 49.9% for Pseudomonas aeruginosa (Almatroudi et al, 2020).…”
Section: Nanocomposite Fe 2 O 3 -Sn 2 O/bcmentioning
confidence: 99%